Transformasi Digital dalam Pendidikan: Meningkatkan Kualitas Pembelajaran Melalui Teknologi - Riska Rahman Tanjung; Annida Azhari Ritonga; Bintang Mahrani Abdullah; Nita Afriani Siregar; Armilah Armilah (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2024)
Digital transformation is changing the paradigm of the world of education and has a major impact on learning and teaching methods. This article discusses key aspects of transformation such as increasing accessibility to information, developing 21st century skills, digital literacy, and various forms of lifelong learning online, distance, and personal. Digital assessments are also an important element in measuring student learning progress. These changes not only bring opportunities but also challenges that require collaboration, innovation and interesting learning experiences. This is very important in understanding the impact of digital transformation on the world of education in order to face rapid technological changes. The research method used in this research is library research obtained from books and journals to ensure the truth. Many changes have occurred along with advances in technology, information comes faster, is easier to learn, and easier to interact with.